Analisis Semantik Doa Kawula Pitados pada Masyarakat Katolik Jawa Yogyakarta: Kajian Etnosemantik - Juan Pius Pratomo (Jurnal Penelitian Pendidikan Agama Katolik, 2026)
This research is driven by a semantic and ethnosemantic understanding of the Kawula Pitados prayer in the Javanese Catholic tradition in Yogyakarta. This prayer not only serves as an expression of faith, but also as a representation of the religious culture of the Javanese Catholic community, particularly in Yogyakarta, which combines elements of local tradition, language, and theology. One of the new aspects of this research is an in-depth analysis using ethnosemantic theory regarding the linguistic relationship in the Kawula Pitados prayer with the Javanese Catholic community. The purpose of this research is to find the relationship between the meaning, interpretation, and role of prayer in shaping Javanese Catholic identity. Prayer text analysis and semantic interpretation were used as qualitative research methods. The result is a mapping of semantic-theological meanings and the relationship between the Kawula Pitados prayer and reverence for Jesus Christ as the Creator, which is also reflected in the Javanese culture of Mikul Duwur Mendhem Jero, which means to uphold, kindness, and honor a respected person. The attitude and actions of Javanese people who always want to glorify those who are more influential, or in the context of prayer, glorify Jesus Christ himself. The results of this study show that the Kawula Pitados prayer reflects the integration of universal Catholic faith with Javanese religious expression, presenting the kawula-gusti relationship as a symbol of submission as well as eschatological hope. Thus, the Kawula Pitados prayer reflects an attitude of respect that is also reflected in Javanese tradition, helping to build religious identity and emphasizing that language functions as a space where theology and culture meet.